Knowledge of Kurdish women about menopause and its related factors: A cross-sectional study in Iraq - Mryam Yaseen Yaseen; Fatema Mohammed Azo; Magroom Esmail Seniar; Hamdia Mirkhan Ahmed; Mahabat Hassan Saeed; Wahida Abdullah Ibraheem; Pshtiwan Dhahir Majeed (Golestan University of Medical Sciences, 2023)
Background: Satisfactory knowledge about menopause is important for women to overcome related challenges. Women with greater knowledge about menopause are more likely to effectively manage its symptoms and navigate this life stage more successfully. This study aimed to determine the level of knowledge of Kurdish women about menopause, as well as to find its association with menopausal status and sociodemographic and obstetrical characteristics. Methods: This cross-sectional study was conducted on perimenopausal (161) and menopausal women (751) who were recruited through non-probability convenient sampling in Kurdistan Region, Iraq, from April to June 2022. For the purpose of the study, a questionnaire was developed that included questions on demographic characteristics, obstetric and menstrual history, and knowledge about menopause. The data were analyzed by frequency, percentage, and chi-square test using SPSS version 25. Ordered logistic regression analysis was performed to determine the effect of demographic and obstetrical factors on some dependent's variables of knowledge. Results: The mean age of menopausal and perimenopausal women was 54.81 ± 5.590 and 46.99±5.688 years, respectively. The participants had more knowledge about the concept and less about the health risks of menopause. On average, menopausal women were more knowledgeable about the definition of menopause compared with perimenopausal women; the difference was highly significant. Overall, the knowledge score indicated that 44% had fair knowledge, 37.6% had poor knowledge, and 18.4% had good knowledge about menopause. Conclusion: Although many women view menopause as a positive life event, it is important to provide them with adequate education, so they can better understand the natural process of menopause to lead a healthy life.